A visualisation technique for network topology transformation within MonALISA monitoring framework. (8th June 2011) - Damian, Andrei; Costan, Alexandru; Cristea, Valentin; Legrand, Iosif
Assessing the network topology and the stability of the links over time proves essential for dealing with many issues of distributed systems. In this paper we present a technique for creating and representing a network topology history. We detail our experience with the implementation of this tool and its integration within the MonALISA framework – a complex dynamic service monitoring system. We illustrate and evaluate its functionality by monitoring high-speed networks, like UltraLight.